Estudo espectroscópico por FTIR da conversão de etanol em catalisadores de Au suportados - Costa, Matheus Soares (Universidade Federal de São Carlos, 2020)
In this work, an FTIR spectroscopic study of gold catalysts supported on monoclinic zirconia (with Au content of 2,5% w/w), was carried out in order to elucidate the surface nature of this catalyst in the dehydrogenation reaction from ethanol to ethyl acetate. In this way, DRIFTS-CO experiments were carried out to probe the gold nanoparticle, which proved to be sensitive to the temperature used in the pretreatment when new species rises when compared to the spectrum of the sample treated at 200 and 500 ºC. This result, added to the group’s previous results, indicates a possible reconstruction of the gold nanoparticle induced by the catalyst treatment temperature. DRIFTS and c-MES studies of ethanol adsorption in pure zirconium oxide and in the catalyst made it possible, by elucidating the active species, to propose a mechanism for the reaction of ethanol dehydrogenation to ethyl acetate on the catalyst surface: (i) Ethanol activation as ethoxide on the zirconia surface; (ii) Activated at the Au-ZrO2 interface, the ethoxide species interact with the gold nanoparticle; (iii) Acethyl species formation by the gold nanoparticle Hβ abstraction from ethoxide adsorbed in the interface region; (iv) ethyl acetate formation by condensation of acethyl with another ethoxide adsorbed in the interface region. DRIFTS analysis of ethanol was in agreement with the proposed mechanism. The effect of catalysts pretreatment temperature was clear in the FTIR spectra by analyzing the species formed in the ethanol adsorption. Furthermore, the phase delay of zirconia surface OH was less reactive at 500 ºC and are related to the ethoxide formation, first stage of ethanol conversion. DFT data of molecular vibrations on the modeled system provided theoretical FTIR spectra for comparison with the experimental signals obtained experimentally.
Spectroscopy study of ethanol conversion in supported gold catalysts by FTIR
Keywords: FTIR; Catalisadores heterogeneos; c-MES; Conversão de etanol; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA